In-depth analysis of genomes and functional genomics of orchid using cutting-edge high-throughput sequencing - Song, Cheng; Wang, Yan; Manzoor, Muhammad Aamir; Mao, Di; Wei, Peipei; Cao, Yunpeng; Zhu, Fucheng (Frontiers in Plant Science, 2022)
High-throughput sequencing technology has facilitated the development of new methodologies and approaches for studying the origin and evolution of plant genomes and subgenomes, population domestication, and functional genomics. Orchids have tens of thousands of members in nature. However, a large-scale gene knockout mutant library and a sophisticated genetic transformation system are still lacking in the improvement of orchid germplasm resources. Here, the research advancements made in orchid molecular biology and genomics over the past decades, including the evolution of genome size divergence and polyploidization, have been discussed. The frequent incorporation of LTR retrotransposons play important roles in the expansion and structural variation of the orchid genome. The large-scale gene duplication event of the nuclear genome generated plenty of recently tandem duplicated genes, which drove the evolution and functional divergency of new genes. The evolution and loss of the plastid genome, which mostly affected genes related to photosynthesis and autotrophy, demonstrated that orchids have experienced more separate transitions to heterotrophy than any other terrestrial plant. The significance of high-throughput sequencing and gene editing technologies in the identification and molecular breeding of the trait-related genes in orchids provides us with a representative trait-improving gene as well as some mechanisms worthy of further investigation. In addition, gene editing has promise for the improvement of orchid genetic transformation and the investigation of gene function. This knowledge may provide a scientific reference and theoretical basis for orchid genome studies.